Evaluation of the emergency preparedness of local authorities in controlling entry of illegal immigrants into the District of Tawau, Sabah - Pat, Kam Seng (2021)
Illegal immigrants movement into the vanous parts of Malaysia, especially the State of Sabah has become an alarming national issue. This is especially true with the vibrant economic growth in Malaysia which has become the main focus for the illegal immigrants. Thus the main objective of this study is to evaluate the capability level of the local authority and its enforcement personnel in managing those threats. The results of the study showed that the local authorities' management system in controlling the influx of illegal immigrants into the District of Tawau only achieved a rating of 0.34 i.e. does not meet the requirements. Meanwhile, the capability level of the enforcement personnel only partially meet the requirement with a mere rating of 0.63. Hence various changes to the present set-up of the local authorities and its enforcement personnel need to be enhanced before the issue become critical.